Competition between Two Modes of 6π‐Photocyclization: A Case Study for 3‐(1,2‐Diarylvinyl)‐2‐arylimidazo[1,2‐a]pyridines - Ustyuzhanin, Alexander O.; Bidusenko, Ivan A.; Kouame, Eric Koffi; Ushakov, Igor A.; Gudovannyy, Alexey O.; Lyssenko, Konstantin A.; Schmidt, Elena Yu; Lvov, Andrey G. (European journal of organic chemistry, 2022)
The photochemical 6π‐electrocyclization of diarylethenes (DAE), 2‐vinylbiaryls (VBA) and their derivatives is widely used in organic synthesis. Combination of these motifs in one molecule opens the issue of selectivity of the photochemical reaction. We have found that upon UV irradiation, 3‐(1,2‐diarylvinyl)‐2‐arylimidazo[1,2‐a]pyridines comprising both DAE and VBA moieties form products of VBA cyclization followed by oxidation. The selectivity of the process was rationalized by DFT calculations. The presented reaction gave access to highly fluorescent 5,6‐diarylnaphtho[1′,2′:4,5]imidazo[1,2‐a]pyridine derivatives. The photocyclization of 3‐(1,2‐diarylvinyl)‐2‐arylimidazo[1,2‐a]pyridines led selectively to fluorescent naphtho[1′,2′:4,5]imidazo[1,2‐a]pyridine derivatives. Such a preference of cyclization on 2‐vinylbiaryl part rather than on diarylethene motif is rationalized by DFT calculations.